Trade and the Environment - Buterbaugh, K. (Encyclopedia of Violence, Peace, & Conflict: Volume 1-4, Third Edition, 2022)
This article focuses on the complex interaction between trade and the environment. The first section reviews the debate among scholars on the environmental effects of trade. Next the article examines the role of the World Trade Organization and how its decisions have impacted the environment. This is followed by a discussion of climate change and its connection to trade. Finally, the article examines multilateral efforts to govern trade and control its environmental consequences as well as to encourage sustainable development. © 2022 Elsevier Inc. All rights reserved.
Keywords: Carbon leakage; Climate change; Comparative advantage; Environmental Kuznets curve; Externality; Free rider problem; Multilateral environmental agreements (MEAs); Nontariff barriers to trade; Pollution haven hypothesis; Prisoner's dilemma; The general agreement on tariffs and trade; World trade organization; dept.psc